South Africa's Savings and Economic Development Linkage: Causal Relationship Examination - Soko, Yohane (Journal of Developing Economies, 2023)
South Africa dreams of eradicating poverty and achieving equitable distribution of its scarce resources among its citizens by 2030. Economic growth sustained over time is crucial in achieving its developmental goals. Domestic savings provide a cheap source of resources for investment that would sustain economic growth. This study explored the relationship between South Africa's aggregate national savings and aggregate national income from 1987 to 2021. The study utilized Solow's bivariate model and error correction-centered causality to ensure the robustness of the study results while testing the relationship between saving and economic growth. The study confirmed that aggregate national saving was positively related to South Africa's economic growth. In the short run, deviations from the long-run paths were partly corrected in the present period. In addition, the study found aggregate national saving Granger caused short- and long-term economic growth. The general policy recommendation is that the Government of South Africa should remove bottlenecks to aggregate national saving mobilization efforts by implementing pro-saving fiscal and monetary policies. High saving rates will stimulate income growth through investments in productive sectors, reducing poverty and inequality.